EKO-PESANTREN TAHFIDZUL QUR’AN DENGAN PENDEKATAN ARSITEKTUR EKOLOGI DI BOYOLALI - Lutfia Brilian Nisa; Wiwik Setyaningsih; Hari Yuliasrso (Universitas Sebelas Maret Surakarta, 2017)
Abstract: Pesantren is an educational institution that focuses on Islamic religious education. Along the changing times, pesantren have evolved both in terms of the curriculum as well as the vision and mission, such as Tahfidzul Qur'an curriculum and environmental concerns curriculum. The Government of Indonesia through the Ministry of Environment in collaboration with the Ministry of Religious Affairs signed a Memorandum of Understanding (MoU) to launch programs eco-pesantren. Pengging, Boyolali is a zone with potential for abundant groundwater discharge. But in some drought, groundwater discharge shrinkage even to cause a reduction in the number of springs. The problems of the Eco-Pesantren Tahfidzul Qur'an is how the effort to plan and design an Eco-Pesantren Tahfidzul Qur'an which facilitate learning and teaching religious knowledge and general knowledge, memorizing the Qur'an, and environmental awareness activities. The existence of Eco-Pesantren Tahfidzul Qur'an aims to fulfill space of teaching and learning religious knowledge and general knowledge, memorizing the Qur'an, and environmental awareness activities. The architectural design method with consideration of Ecological Architecture approach is capable of displaying eco-friendly themed activities promoted by Eco-Pesantren Tahfidzul Qur'an. The concept of Eco-Pesantren Tahfidzul Qur'an will apply the concept of Ecological Architecture approach that includes zone concept space, building orientation, processing site, as well as the concept of architectural approach in the application of eco-pesantren. Keywords: Architecture, Ecology, Eco-Pesantren, Education